Correlation between the apex of lumbar lordosis and pelvic incidence in asymptomatic adult - Pan, Changyu; Wang, Guodong; Sun, Jianmin (European spine journal, 2020)
Purpose The objective of this study was to test the correlation between the apex of lumbar lordosis (LLA) and pelvic incidence (PI) in asymptomatic adults, and to establish predictive formulae based on the PI to obtain the reference values of lumbar sagittal parameters. Methods A cohort of 183 asymptomatic volunteers older than 18 years was enrolled in this study between April 2017 and May 2019. A full-spine, standing X-ray was taken for each subject. The following parameters in the sagittal plane were measured: the LLA, the distance between the plumb line of the lumbar apex (LAPL) and gravity plumb line, lumbar lordosis (LL), the upper arc of lumbar lordosis (LLUA), the lower arc of lumbar lordosis (LLLA) and the PI. The correlations between lumbar parameters and PI were analysed, and simple linear regressions were simultaneously constructed. The statistical significance level was P < 0.05. Results The PI was statistically correlated with the LLA ( r s = − 0.595, P < 0.001), LAPL ( r s = 0.503, P < 0.001), LL ( r s = 0.605, P < 0.001), LLUA ( r = 0.354, P < 0.001) and the LLLA ( r = 0.658, P < 0.001). The corresponding regression formulae were as follows: LLA = − 0.042*PI + 6.134 ( R 2 = 0.306), LAPL = 0.448*PI + 26.570 ( R 2 = 0.279), LL = 0.888*PI − 2.667 ( R 2 = 0.370), LLUA = 0.272*PI − 2.297 ( R 2 = 0.126) and LLLA = 0.607*PI + 0.177 ( R 2 = 0.433). Conclusion The PI has strong correlations with the LLA, LAPL, LL, LLUA and LLLA, which demonstrates that the specific lumbar shape can be affected by the pelvic morphology. Moreover, predictive models for ideal lumbar sagittal parameters based on the PI have been developed, contributing to the design of precise and individualized preoperative plans. Graphic abstract These slides can be retrieved under Electronic Supplementary Material.